IMPLEMENTATION OF THE INDEPENDENT CAMPUS LEARNING PROGRAM IN CREATING QUALITY GRADUATES AND CHARACTER IN THE GLOBAL COMPETITIVENESS OF THE WORLD - Arif Rohman Hakim; Ian Harum Prasasti (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
The independent campus development program is a policy to obtain the relevance of teaching, training and education in higher education which focuses on the needs of science and the world of work, as well as campus life and its relation to the socio-cultural aspects of society and national life, which will be an effort to foster potential generations. The purpose of this study is to examine the implementation of the independent campus learning program in creating quality and character graduates who are able to keep up with the competitiveness of human resources in a globalized world. This type of research is literature review research with data sources used relevant sources such as books, official documents, publications, and relevant research results. The results of the study show that the MBKM program has a positive impact on students to create quality and character graduates who are able to participate in the competitiveness of human resources. The MBKM program provides experience and opportunities for students to hone skills according to their talents and interests by going directly into the world of work as preparation for future careers. The success of the MBKM program to achieve its goals can be influenced by the collaboration between stakeholders and students in its implementation.